Contribution to the knowledge of the Coccinellidae (Insecta: Coleoptera) fauna from the Azores islands. - Soares, António O. (2008)
An updated list of the Coccinellidae species of the Azores archipelago is presented. New records for S. Miguel: Nephus (Sidis) hiekei; Sta. Maria: Rodolia cardinalis; S. Jorge: Stethorus punctilium, Clitosthetus arcuatus, Scymnus nubilus, N. (Sidis) hiekei; Pico: R. cardinalis; Graciosa: C. arcuatus, S. (Scymnus) interruptus, N. (Sidis) hiekei, Lindorus lophantae and R. cardinalis; Corvo: S. nubilus, N. (Sidis) hiekei and Coccinella undecimpunctata. Regressions of species richness against area of the islands and distance from the nearest mainland were performed. No statistical significant correlation between species richness against area was found but a statistical significant negative correlation between the number of species and the distance from the nearest mainland was obtained. The results are, in part, in accordance with the predictions of MACARTHUR & WILSON’S (1967) equilibrium theory of island biogeography, relating differences in the diversity within Azorean islands with isolation.